2020
DOI: 10.1111/ele.13473
|View full text |Cite
|
Sign up to set email alerts
|

A native apex predator limits an invasive mesopredator and protects native prey: Tasmanian devils protecting bandicoots from cats

Abstract: Apex predators can limit the abundance and behaviour of mesopredators, thereby reducing predation on smaller species. We know less about whether native apex predators are effective in suppressing invasive mesopredators, a major global driver of vertebrate extinctions. We use the severe disease‐induced decline of an apex predator, the Tasmanian devil, as a natural experiment to test whether devils limit abundance of invasive feral cats and in turn protect smaller native prey. Cat abundance was c. 58% higher whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 91 publications
(147 reference statements)
0
39
0
Order By: Relevance
“…Although the outlook for the wild devil population is undoubtedly more positive than it was a decade ago (McCallum et al 2009), devils are currently well below ecologically functional densities across much of Tasmania. Devil declines have had cascading ecological effects, such as carrion accumulation (Cunningham et al 2018), mesopredator release with effects on small and medium-sized mammals (Hollings et al 2014;Hollings et al 2016;Cunningham et al 2020), and the relaxation of anti-predator behaviours by prey (Hollings et al 2015;Cunningham et al 2019a;Cunningham et al 2019b). In the the online data repository, we provide annual rasters of estimated devil densities from 1985 to 2035, which we expect will be useful for improving our understanding of the ecological effects of devils and identifying thresholds that could provide longer term targets for population recovery.…”
Section: Population Trends and Conservationmentioning
confidence: 99%
“…Although the outlook for the wild devil population is undoubtedly more positive than it was a decade ago (McCallum et al 2009), devils are currently well below ecologically functional densities across much of Tasmania. Devil declines have had cascading ecological effects, such as carrion accumulation (Cunningham et al 2018), mesopredator release with effects on small and medium-sized mammals (Hollings et al 2014;Hollings et al 2016;Cunningham et al 2020), and the relaxation of anti-predator behaviours by prey (Hollings et al 2015;Cunningham et al 2019a;Cunningham et al 2019b). In the the online data repository, we provide annual rasters of estimated devil densities from 1985 to 2035, which we expect will be useful for improving our understanding of the ecological effects of devils and identifying thresholds that could provide longer term targets for population recovery.…”
Section: Population Trends and Conservationmentioning
confidence: 99%
“…In comparison, DFT2 was identified in 2014 in a small region of South‐East Tasmania and is yet to become wide‐spread 7,11 . Conservation of the Tasmanian devil is considered a priority due to the status of the species as an apex predator and its role as a competitor of introduced pests, such as feral cats 12 . Recent studies have identified a small subset of devils with natural tumour regressions 13 .…”
Section: Introductionmentioning
confidence: 99%
“…7,11 Conservation of the Tasmanian devil is considered a priority due to the status of the species as an apex predator and its role as a competitor of introduced pests, such as feral cats. 12 Recent studies have identified a small subset of devils with natural tumour regressions. 13 However, these natural regressions remain rare, and to date there has been no sustainable population recovery.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mesoscavengers were attracted to wolf kills yet were negatively associated with wolf density at the landscape scale [19]. Although carcasses are attractive to mesoscavengers, predator avoidance plays an important role in shaping carnivore communities [18, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Across the southern-temperate continental island of Tasmania (Australia) and its large offshore islands (Fig. 1; total area: 68,401 km), a large-scale natural experiment is occurring due to the severe population decline of the largest extant terrestrial carnivore, the marsupial Tasmanian devil Sarcophilus harrisii [20]. Devils are Tasmania’s dominant scavenger, being both the largest extant terrestrial mammalian carnivore and a specialist, although facultative, scavenger adapted for processing the toughest parts of carcasses [21].…”
Section: Introductionmentioning
confidence: 99%